2021
DOI: 10.1002/wer.1659
|View full text |Cite
|
Sign up to set email alerts
|

Green production of hydrochar nut group from waste materials in subcritical water medium and investigation of their adsorption performance for crystal violet

Abstract: This study evaluates the production of hydrochars from the outer shells of the nut group (peanut, hazelnut, walnut, and pistachio) in an eco-friendly subcritical water medium (SWM) and their effects as adsorbents on the removal of crystal violet (CV) from an aqueous solution. The prepared hydrochars were characterized using Brunauer Emmett-Teller (BET) analysis, scanning electron microscope (SEM), Fourier transforms infrared spectroscopy (FTIR), and zeta potential. The adsorption process was optimized based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The dye adsorption capacity of tomato stem ash increased with decreasing particle size. As the particle size decreases, the surface area increases and effectively affects the adsorption of the pollutants 42 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dye adsorption capacity of tomato stem ash increased with decreasing particle size. As the particle size decreases, the surface area increases and effectively affects the adsorption of the pollutants 42 …”
Section: Resultsmentioning
confidence: 99%
“…As the particle size decreases, the surface area increases and effectively affects the adsorption of the pollutants. 42 F I G U R E 6 The effect of solution pH value on the adsorption process using tomato stem.…”
Section: Effect Of Particle Size On Removal Of Po 3àmentioning
confidence: 99%
“…Several researchers found that the pseudo‐second‐order model can describe the adsorption of dyes better than Lagergren's pseudo‐first‐order (Isik, Saleh, Bilici, & Dizge, 2021; Yalvaç et al, 2021). Saleh, Isik, Yabalak, et al (2021) prepared hydrochars from nuts group for crystal violet adsorption. All of the prepared hydrochars were found to follow the pseudo‐second‐order model.…”
Section: Resultsmentioning
confidence: 99%
“…However, many researchers have explored the adsorbent abilities of different material types to achieve better results at lower costs (Deb et al, 2020). Bio adsorbents (Gupta, 2009), zeolite (Brião et al, 2018), metal–organic frameworks (Xin et al, 2013), alumina (Banerjee et al, 2019), covalent organic frameworks (He et al, 2021), biochar (Ahmad et al, 2020), two‐dimensional materials (MXene) (Sun et al, 2021; Yang et al, 2021), modified activated carbon (Ho et al, 2019), and hydrochar (Saleh, Isik, Yabalak, et al, 2021) were broadly examined. Leonardite is the oxidation product of low‐quality coal (lignite) during carbonization.…”
Section: Introductionmentioning
confidence: 99%
“…Using various technologies, such as pyrolysis [ 3 ], combustion [ 4 ], anaerobic digestion [ 4 , 5 ], fermentation [ 6 ], etc., biowastes can be valorized into biofuels [ 7 , 8 ], bio-oil [ 9 ], valuable chemicals [ 10 , 11 ], and activated carbon-based adsorbents [ 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%